Identification of novel nucleus pulposus markers: Interspecies variations and implications for cell-based therapiesfor intervertebral disc degeneration - Rodrigues-Pinto, R. (2013)
Mesenchymal stem-cell based therapies have been proposed as novel treatments for intervertebral disc degeneration, a prevalent and disabling condition associated with back pain. The development of these treatment strategies, however, has been hindered by the incomplete understanding of the human nucleus pulposus phenotype and by an inaccurate interpretation and translation of animal to human research. This review summarises recent work characterising the nucleus pulposus phenotype in different animal models and in humans and integrates their findings with the anatomical and physiological differences between these species. Understanding this phenotype is paramount to guarantee that implanted cells restore the native functions of the intervertebral disc.